2021
DOI: 10.3390/audiolres11040047
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Inner Ear Malformations: A Review

Abstract: Inner ear malformations are present in 20% of patients with sensorineural hearing loss. Although the first descriptions date to the 18th century, in recent years the knowledge about these conditions has experienced terrific improvement. Currently, most of these conditions have a rehabilitative option. Much less is known about the etiology of these anomalies. In particular, the evolution of genetics has provided new data about the possible relationship between inner ear malformations and genetic anomalies. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
0
5
0
5
Order By: Relevance
“…For example, CND has been reported in patients with CHARGE, VACTERL, and Coffin‐Siris syndromes, 51‐53 which are hereditary and associated with USNHL 54 . Furthermore, multiple genes have been documented involved in inner ear malformations in syndromic and nonsyndromic SNHL 55,56 . Therefore, considering the aggregation of patients with USNHL in multiplex families and the potential association between USNHL and genetics‐related CND and inner ear malformations, it is inferred that the genetic component of USNHL may be higher than what was demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CND has been reported in patients with CHARGE, VACTERL, and Coffin‐Siris syndromes, 51‐53 which are hereditary and associated with USNHL 54 . Furthermore, multiple genes have been documented involved in inner ear malformations in syndromic and nonsyndromic SNHL 55,56 . Therefore, considering the aggregation of patients with USNHL in multiplex families and the potential association between USNHL and genetics‐related CND and inner ear malformations, it is inferred that the genetic component of USNHL may be higher than what was demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 Los genes FGF3 y HOXA 1 están asociados con aplasia laberíntica, que se produce durante la tercera semana de gestación, sin embargo, también se relacionan con otros síndromes, como el de aplasia laberíntica, microtia y microdoncia (LAMM), y síndrome de mutación HOXA1, caracterizado por aplasia de la carótida bilateral, retraso en el crecimiento y alteraciones oculares. 15 Lo anterior podría indicar en el caso de nuestra paciente un tipo de herencia poligénica, dada la afección a nivel articular y cardíaco en conjunto con las características clínicas clásicas del síndrome.…”
Section: Discussionunclassified
“…In a recent study, more than 70% of patients demonstrated vestibular symptoms, of which 17% had bilateral vestibular areflexia on caloric stimulation while 10% showed no signs of vestibular dysfunction on caloric stimulation (25). In Pendred's syndrome, associated with mutations of the SLC26A4 gene, the incomplete partition type II constitutes a characterizing element of the malformative spectrum, together with the presence of an enlarged vestibular aqueduct and thyroid goiter (27).…”
Section: Incomplete Partition Type IImentioning
confidence: 99%